The Influence of Price and Product Quality on Consumer Satisfaction on Oppo Smartphones on Shopee - Dani Akbar Maulana; Haikal Musyaffa; Yusuf; Tiara Mushiarsih (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of price and product quality on consumer satisfaction with Oppo smartphones on Shopee. The research method used is quantitative, with data collected through questionnaires distributed to university students in Cirebon. The data was analyzed using multiple linear regression with the assistance of SPSS software. The results of the study indicate that both price and product quality significantly influence consumer satisfaction, both partially and simultaneously. Partially, price has a greater influence than product quality. The coefficient of determination (R²) value of 0.255 indicates that 25.5% of the variation in consumer satisfaction can be explained by price and product quality, while the remaining variation is influenced by other factors. The conclusion of this study emphasizes the importance of competitive pricing strategies and product quality improvements to enhance consumer satisfaction with Oppo smartphones on Shopee.